2022
DOI: 10.1088/1748-9326/ac52c7
|View full text |Cite
|
Sign up to set email alerts
|

Improved sustainability assessment of the G20’s supply chains of materials, fuels, and food

Abstract: Transparency in global value chains of materials, fuels, and food is critical for the implementation of sustainability policies. Such policies should be led by the G20, who represent more than 80% of global material, fuel, and food consumption. Multi-regional input-output (MRIO) analysis plays an important role for consumption-based assessment, including supply chains and their environmental impacts. However, previous accounting schemes were unable to fully assess the impacts of materials, fuels, and food. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 64 publications
(100 reference statements)
3
13
0
Order By: Relevance
“…Overall, more than half of global coal-mining related biodiversity loss is related to heat and electricity supply to manufacture metals (29%), cement (10%), chemicals (10%), and plastics (5%). This is in accordance to previous studies showing that many climate and particulate-matter related health impacts of coal combustion are induced in China and India 42,50 , with a rising fraction related to material production (mostly cement, steel and plastics for building their infrastructure and supplying the global market).…”
Section: Infrastructuresupporting
confidence: 93%
See 2 more Smart Citations
“…Overall, more than half of global coal-mining related biodiversity loss is related to heat and electricity supply to manufacture metals (29%), cement (10%), chemicals (10%), and plastics (5%). This is in accordance to previous studies showing that many climate and particulate-matter related health impacts of coal combustion are induced in China and India 42,50 , with a rising fraction related to material production (mostly cement, steel and plastics for building their infrastructure and supplying the global market).…”
Section: Infrastructuresupporting
confidence: 93%
“…While Werner et al 41 found that mining quantity is a reasonable proxy for mining area (based on a mining dataset of 3'633 km 2 ), our results indicate that for most countries and mining products, neither quantity is suitable to predict mining area, nor is mining area appropriate to estimate biodiversity loss. Furthermore, our results show that hotspots of biodiversity loss differ from other environmental impacts of mining products, such as climate and particulate-matter related health impacts, dominated by China's steel and cement production 42 . This highlights the importance of considering local biodiversity loss of land use to promote sustainable practices in the mining and metals industry.…”
Section: Figurementioning
confidence: 78%
See 1 more Smart Citation
“…36,49 Furthermore, our results show that hotspots of biodiversity loss differ from other environmental impacts of mining products, such as climate and particulate matter-related health impacts, dominated by China's steel and cement production. 50 This highlights the importance of taking the local biodiversity loss of land use into consideration to promote sustainable practices in the mining and metal industry.…”
Section: Resultsmentioning
confidence: 99%
“…This fraction is significantly lower than that for the climate impacts of metals, which are dominated by steel production (>80%), mostly because of coal combustion. 50 The link between metal mining and processing countries shows that most biodiversity loss is induced in a country other than where metals are further processed (Figure 4a,b). Similarly, most metals are processed in a country other than where they are finally consumed (Figure 4b,c).…”
Section: Resultsmentioning
confidence: 99%